Measures of Excess Demand and Unemployment in Canada and the United States - Siebert, Calvin; Zaidi, Mahmood (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1994)
The authors consider the reasons for the shifts in the unemployment vacancy (UV) relationship in Canada and the United States during the past two decades to see whether these shifts can explain the gap in the unemployment between the two countries which arose about 1980 and may be increasing. We find that changing structural imbalances in the labor markets by themselves cannot explain the shifts in the UV curves or the gap in the unemployment rates in the two countries. We conclude that aggregate economie shocks which create some structural imbalances are required to explain the shifts in the UV curves and the differing unemployment experiences in the two economies.